Feasibility of interim fish production in water-harvesting tanks in rainfed drought-prone areas - Paul, D K (Indian Journal of Fisheries, 2011)
In watershed management project a portionof the cultivable \VKA is converted into asmall reservoir or water-harvesting tank. Toincrease the {Hofit Aom such farm ponds,intÂ»im fish production was tried along withcrop production.